7Be behaviour and meteorological conditions associated with 7Be peak events in Spain. (January 2017) - Hernández-Ceballos, M.A.; Brattich, E.; Lozano, R.L.; Cinelli, G.
Abstract: This work regards a comprehensive analysis of the overall distribution of 7 Be activity concentrations in Spain and the synoptic meteorological conditions associated with the highest 7 Be peaks (>8 mBq/m 3 ). The use of four sampling stations (Barcelona, Bilbao, Madrid, and Sevilla) included in REMdb, with different latitudinal location, as well as the relatively long time period used in this study (2001–2010), allowed to improve the understanding of 7 Be spatio-temporal distribution in Spain. The comparison of the 7 Be activity concentrations mean values indicated a north-south gradient (from 3.1 ± 1.1 mBq/m 3 in Bilbao to 4.0 ± 1.8 mBq/m 3 in Sevilla), even though not statistically significant (as indicated by the t-test). However, the analysis of frequency distributions and temporal evolutions of 7 Be activity concentrations have suggested the presence of two main areas, namely northern (Bilbao and Barcelona) and southern (Sevilla) Spain. The identification and analysis of periods associated with the highest values of 7 Be have allowed studying the different synoptic patterns associated with stratospheric–tropospheric transport (STT). In particular, three episodes (one in the north and two in the south) potentially associated with vigorous STT have been identified and analysed in detail. The results displayed that the omega block configuration, extending either over western Russia and Scandinavia or into the Atlantic Ocean, forced the prevailing jet stream to the northeast and south of Spain respectively with subsequent subsidence. In summer, this blocking configuration at high latitudes was combined with the presence of the Azores high pressure system to the west of Spain, affecting the 7 Be activity concentration recorded in the south. Highlights: Overall analysis of 7 Be distribution in Spain. Identification of northern and southern areas based on 7 Be values. Analysis of synoptic meteorological patterns associated with 7 Be peaks. Meteorological analysis of vigorous STT associated with 7 Be peaks.